The Zionist Lobby And Its Impact On American Foreign Policy A Case Study Of The War On Syria - اسماعيل عصام; لايقه رامي; أبو العبد أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2021)
American foreign policy is closely related to domestic politics, and is influenced by many official institutions And informal, at the level of foreign decision-makers, the White House, represented by the President and his advisers, foreign ministers, the Ministry of Defense, and the US Congress, plays an influential role in directing and implementing American foreign policy, and interest and pressure groups, led by the Zionist lobby, play a major role in influencing these institutions. Relations between the United States of America and the Zionist entity went through several stages, in which the Zionist lobby played an extreme and influential role in the orientations of American policy towards the Arab-Zionist conflict in the Middle East before the declaration of the Zionist entity in1948 until now. The American strategy has met with the Israeli strategic role in the Middle East, which can achieve American interests through mutual agreement on many principles such as preserving the security of the Zionist entity and pressure on Arab countries to recognize it and classify the United States of America as a major ally of the Zionist entity and secure states’ access United and its allies on oil supplies in the Middle East. Syria being one of the Arab countries and within the countries of the Middle East was the focus of attention of the United States of America and the Zionist entity in particular Through this study, we are trying to clarify the role of this lobby in incitement and the recent war on Syria and the interests and gains that the Zionist entity has achieved from this war.